Multi-attribute decomposition of required level of machine utilization of combine harvesters (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
Multi-attribute decomposition includes component decomposition, functional decomposition, decomposition by the attribute of the type of component and decomposition by the attribute of the phenomenon that occurs in the system of machine utilization of combine harvesters. Functional decomposition is important, since the study of the system of machine utilization of combine harvesters should be limited to considering the reliability of individual modules. The consideration should cover the system as a whole. The reliability of the system of machine utilization of combine harvesters is determined by the combination of the reliability of its individual elements. The question arises of the nature of this combination. Usually, one system of machine utilization of combine harvesters performs several functions. Along with the function of controlling the parameters of the object of machine utilization of combine harvesters, it can also perform other functions. To determine the reliability of the system of machine utilization of combine harvesters, it is necessary to determine which elements participate in the performance of certain functions. Taking into account the indicators of the importance of the modules of the machine utilization system of grain harvesters allows, firstly, to modify the order of module reservation, ensuring higher reliability of important functions, and secondly, to obtain a more accurate assessment of the probability of failure-free operation, deriving data on the failure-free operation not only of the entire system, but also of the main function separately. This technique provides an increase in the failure-free operation of selected system functions, but with this indicator, other parameters should also be taken into account for the formation of the system, in particular, the risk of failures.
Keywords: combine harvester; machine use; methodology; decomposition